The structure-activity relationship of Vitamin B12 and cobalamins and their nutritional correlations (Research, Society and Development, 2023)
This article reviews the so-called “cobalamins”, with special emphasis on coenzyme B12, discussing aspects of its structure-function relationship as well as various implications in biochemical, physiological and nutritional areas. Despite being one of the micronutrients with the lowest presence in organisms, cobalt (Co) is a constituent part of highly relevant enzymatic cofactors and associated with various biochemical and/or enzymatic processes. Vitamin B12 really represents a focus of interest of a multi- and interdisciplinary nature, since it is a metallic complex, an organometallic compound (for example, in the methylcobalamin form we identify the Cobalt-Carbon (Co-C) bond) and a group of relevance biophysics, as it interacts with different proteins in the biological environment, in addition to its impactful nutritional role, the deficiency of which causes the so-called “pernicious anemia”. This literature review article aims to offer a general and interdisciplinary overview of the topic, covering relevant topics in cobalt chemistry, mainly its coordination chemistry, which have been considered as model systems both for the study of metallic complexes properly considered and for the evaluation of the structure- metalloprotein activity.